Tourism a temporal analysis
"Examines how temporality manifests in and impacts tourism in different parts of the world looking at climate, culture and/or structural conditions of the tourism operation. It looks at the reasons and causes for temporality within tourism and how this effects both the industry, the consumer and the environment. Divided into four parts, Tourism: A temporal analysis looks at: * The dimensions and relationships between time and tourism: the causal reasons for seasonality in tourism, links between seasonal variations and visitation and why people travel when they do. * The operational dimensions of temporality: the challenges of 'peak season' and 'low season', pricing, planning, managing the labour demands and yield systems. * Strategic responses to temporal variation: the role of temporality/seasonal variation as a policy issue, the role of festivals and events in combatting temporality and the effect of social media. * The End of Temporality?: the rise of 'year-round ' tourism, its enablers and its' resulting effects both positive nad negative in the industry, the environments and the economy. With contributions from international experts from academia and industry, this text uses case students and vignettes throughout to contextualise the theory and enabling students to have a better understanding in order to critique and question the issues discussed." --